An efficient and facile synthesis of deuterium‐labeled anticancer agent bendamustine hydrochloride. (28th May 2018) - Liu, Baomin; Qin, Hui; Zhang, Yinsheng
Abstract : Bendamustine hydrochloride is an alkylating agent that was developed for the treatment of various human cancers. The stable isotope‐labeled bendamustine was required to support clinic studies. An effective and operationally simple method for the synthesis of [D6 ] bendamustine hydrochloride was developed using DCl as a catalyst and D2 O as a deuterium source. Under the present condition, regioselectively deuterated bendamustine hydrochloride with high deuterium incorporation is achieved. Abstract : The stable isotope‐labeled bendamustine was required to support clinic studies. An effective and operationally simple method for the synthesis of [D6 ] bendamustine hydrochloride was developed using DCl as a catalyst and D2 O as a deuterium source. Under the present condition, regioselectively deuterated bendamustine hydrochloride with high deuterium incorporation is achieved.